State-dependent effects of tax changes in Germany and the United Kingdom - Bernd Hayo; Sascha Mierzwa (Philipps-University Marburg, School of Business and Economics, 2021)
We study state-dependent effects of narratively identified tax shocks in Germany and the UK over the period 1974Q1-2018Q4 using local projections. In addition, we distinguish between aggregated and disaggregated tax types (direct and indirect taxes) as well as look for possible asymmetries between tax hikes and tax cuts. We find a number of differences across the business cycle, and between sample countries, tax types, and direction of tax changes. For instance, aggregated tax cuts initially have a larger effect during times of nonrecession in Germany, whereas we find no state-dependent effects for the UK. When disaggregating tax types, German indirect tax cuts only appear expansionary during downturns, whereas the effect is positive throughout the business cycle in the UK. Furthermore, we find different reactions when considering tax cuts and hikes individually: tax hikes can be expansionary in Germany (UK) when implemented during non-recessionary (recessionary) periods whereas they are contractionary during recessions (non-recessions). When considering tax cuts, German GDP rises only when cuts are enacted in times of non-recession, whereas in the UK, the reactions is positive in either case and mostly symmetric. All these findings are robust to various changes in the econometric setup.
Keywords: E62; E63; H20; H30; K34; 330; Fiscal policy; tax policy; legislated tax changes; state dependence; direct taxes; indirect taxes; asymmetric effects; Germany; United Kingdom; local projections; narrative approach